Human responses to wave slamming vibration on a polar supply and research vessel. (February 2018) - Omer, H.; Bekker, A.
Abstract: A polar supply and research vessel is pre-disposed to wave slamming which has caused complaints among crew and researchers regarding interference with sleep, equipment use and research activities. The present work undertook to survey passenger claims of sleep interference, disturbed motor tasks and equipment damage as a result of wave slamming during normal operations of this vessel. The hypothesis was investigated that whole-body vibration metrics from ISO 2631-1 are potentially suitable for the prediction of human slamming complaints. Full-scale acceleration measurements were performed and wave slamming events were subsequently identified from the human weighted acceleration time histories. A daily diary survey was also conducted to gather the human response. The vibration caused by wave slamming was found to be strongly correlated with sleep disturbances and activity interference. Sleep and equipment use were found to be the most affected parameters by slamming. Daily vibration dose values were determined by accumulating the vibration as a result of slamming over 24 h periods. This metric accounted for increased magnitudes and frequency of slamming incidents and proved to be the best metric to represent human responses to slamming vibration. The greatest percentage of activities affected by slamming related to sleep regardless of daily cumulative VDV magnitude. More than 50% of the recorded responses related to sleep when the daily cumulative VDV ranged between 8.0 m/s 1.75 –10.0 m/s 1.75 . The peak vertical vibration levels recorded on the vessel reach magnitudes which are associated with sleep disturbance in environments where acoustic noise is present. Highlights: A research vessel is prone to wave slamming causing passenger complaints. Sleep interference, disturbed motor tasks and equipment damage were surveyed. Whole-body vibration was measured and metrics from ISO 2631-1 were calculated. Whole-body vibration caused by wave slamming is correlated to sleep disturbances. Daily vibration dose values are best correlated to human responses to slamming vibration.